THE RELATIONSHIP BETWEEN SLAVERY AND RACIAL DISCRIMINATION ILLUSTRATED ON THE BIRTH OF NATION (2016) MOVIE - Pratiwi, Ulva; Permatasari, Riana (Elite : English and Literature Journal, 2022)
This paper focuses on analyzing the relationship between slavery and racial discrimination illustrated in The Birth of a Nation movie by Nate Parker. This paper has two purposes, the first purpose is to explain how slavery happen to all black characters. Meanwhile, the second purpose is to analyze how racial discrimination was experienced by all black characters in the movie. In analyzing, this paper used the qualitative research method. The movie script The Birth of a Nation was to be the primary data. Furthermore, several supporting data taken from books, journals, e-journal, and internet sites were to be the secondary data. Whereas, the result of this study has proved that all black characters in The Birth of a Nation movie were enslaved such as be planters, carpenters, laborers, and servants by white people. Not only enslaved, but they also experienced racial discrimination treatment such as injured, tortured even killed, and raped. The racial discrimination that happened to them was indicated as the effects of slavery or as the consequence to be slaves.